Early childhood teachers' perceptions of the social validity of the incredible years teacher classroom management programme in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the Master of Educational Psychology at Massey University, Manawatū, New Zealand - Wooller, Sally Kay (Massey University, 2015)
The Incredible Years Teacher Classroom Management (IY TCM) programme is being offered to teachers of young children in Aotearoa New Zealand by the Ministry of Education to support the provision of more positive learning environments and provide teachers with strategies to promote pro-social behaviour and decrease disruptive behaviour. An important aspect of the implementation of any programme is its social validity with its intended users. Establishing the social validity of an intervention or prevention programme is important as it impacts on its implementation and sustainability within the intended setting. The present study explored three aspects of social validity of the IY TCM programme by examining early childhood teachers perspectives about a) the alignment between IY TCM principles and strategies and the early childhood curriculum, Te Whariki; b) the appropriateness of IY TCM principles and strategies to the New Zealand context and their teaching practice; and c) the ways in which teachers incorporate IY TCM principles and strategies into their teaching practice. Placed within a constructivist epistemology and using a mixed methods approach, a web based, anonymous survey was conducted. One hundred and seven early childhood teachers who had participated in IY TCM participated. Results indicated that most early childhood teachers in Aotearoa New Zealand find IY TCM principles and strategies to align with Te Whariki, particularly in the areas of Relationships, Empowerment and Family and Community, with IY TCM improving some teachers’ implementation of Te Whariki. Discussion of both favourable and less favourable views about the social validity of IY TCM contribute to understanding potential ways to help strengthen and support implementation of IY TCM strategies in early childhood centres, as well as ways to improve programme training for teachers. Limitations of the research and future directions for research are identified.
Keywords: Incredible Years Teacher Classroom Management Programme; Early childhood education; Classroom management; Social aspects; Early childhood teachers; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education